Rare Cause of Lower Gastrointestinal Bleeding—Case Presentation and Literature Review - Cristian Iorga; Cristina Raluca Iorga (Reports)
Background and Clinical Significance: Gastrointestinal bleeding is a critical medical emergency, with upper gastrointestinal bleeding occurring approximately five times more frequently than lower gastrointestinal bleeding (LGIB). The incidence of LGIB tends to increase with age, likely due to a greater prevalence of vascular and diverticular diseases among older patients. However, there are rare or extremely rare causes of LGIB that demand significant diagnostic and therapeutic efforts, some of which may pose unexpected challenges during surgery. Case report: We present the case of a 75-year-old woman, previously treated for a cecal neoplasm 15 years ago, who was hospitalized due to intermittent lower gastrointestinal bleeding over the past three months. Initially, the patient declined a colonoscopic examination, and the bleeding stopped spontaneously. She was then discharged at her own request in stable condition. However, she returned with a recurrence of the bleeding. While preparing for a colonoscopy, she experienced subocclusive symptoms, abdominal distension, and vomiting. During emergency surgery, a floating coprolith, which was attached to one of the anastomosis sutures, was sensed through palpation and later confirmed via colotomy. The coprolith was removed, and hemostasis was achieved in situ, leading to a favorable postoperative recovery and normalization of intestinal transit. A literature review identified 24 articles that met the eligibility criteria concerning rare causes of LGIB. Appendiceal bleeding (due to erosions, arteriovenous malformations, or endometriosis) was the most common cause, whereas the rarest causes included jejunal hemangiomas and rectal ulcers resulting from mucormycosis. Diagnosing these conditions is often challenging, typically requiring CT scans, colonoscopy, and angiography, with surgical treatment being the primary method to ensure hemostasis. In conclusion, the diagnosis and management of LGIB present significant challenges for clinicians, and successful outcomes are usually achieved through a collaborative multidisciplinary team approach.